God, love, and death of Trunyan Village - Audyandari, Ni Kadek Niyanda (Institute for Advanced Science Social, and Sustainable Future, 2024)
Background: Trunyan Village is a traditional village on the shores of Lake Batur in Bali, Indonesia. The village has unique funeral traditions and religious beliefs. The